Sex-specific attenuation of constant light-induced memory impairment and Clock gene expression in brain in hepatic Npas2 knockout mice - Ruby Chrisp; Mitchell Masterson; Rebecca Pope; Christopher J. Roberts; Hilary M. Collins; David J. G. Watson; Derek O’Neil; Kjersti M. Aagaard; Claire L. Gibson; David M. Heery; Paula M. Moran (Scientific Reports)
Abstract NPAS2 (Neuronal PAS Domain Protein 2) is a component of the core circadian clock and the coordinated activity between central brain and peripheral liver clock proteins postulated to be instrumental for linking behaviour and metabolism. We investigated a conditional liver-specific knockout mouse model (Npas2-/- or cKO) to explore its function in activity, circadian rhythms and cognition (novel object recognition-NOR). Circadian rhythms showed no genotype differences. Constant-light reduced NOR in floxxed controls but remarkably not in Npas2-/- mice, particularly females. Consistent with entrainment of systemic and central circadian biology, N pas2-/- mice showed altered expression of circadian gene Clock in frontal cortex. Sex differences independent of genotype were found in expression of circadian genes Clock, Bmal1 and Reverb-b in brain. Sex differences in Clock were absent in N pas2-/- mice. Females showed greater period length and phase response to constant light independently of genotype. The data suggest that a role for peripheral NPAS2 in constant light-induced memory impairment in females, and potential mediation by altered cortical circadian Clock gene expression, merit further investigation. These findings have implications for the interaction between peripheral and central circadian clocks, circadian sex differences and the deleterious effects of constant light on cognition.